+0  
 
0
867
2
avatar

If 3n + 1 is a perfect square, show that n + 1 is the sum of three perfect squares.

Guest Nov 27, 2015

Best Answer 

 #1
avatar+20549 
+35

If 3n + 1 is a perfect square, show that n + 1 is the sum of three perfect squares.

 

3n + 1 is a perfect square:

\(\small{ \begin{array}{rcl} 3n+1 &=& a^2 \\ 3n &=& a^2 - 1 \\ n &=& \frac{a^2-1}{3}\\ \hline n+1 &=& \frac{a^2-1}{3} +1 \\ n+1 &=& \frac{a^2-1+3}{3}\\ n+1 &=& \frac{a^2+2}{3}\\ \end{array} }\)

 

Because \(\frac{a^2+2}{3}\) is a integer then \(a^2+2\) is divisible by 3, then \(a^2\) is not divisible by 3  and also \(a\) is not divisible by 3,

because if 3 is not a prime factor in \(a^2\) a perfect spuare, then 3 is not a prime factor in  \(a\)

 

Two numbers are not divisible by 3. It is  \(3b +1\) and \(3b + 2\)

 

1. We substitute \(a = 3b+1\)

\(\small{ \begin{array}{rcl} n+1 &=& \frac{a^2+2}{3}\qquad \text{substitute }\ a = 3b+1\\ n+1 &=& \frac{(3b+1)^2+2}{3} \\ n+1 &=& \frac{9b^2+6b+1+2}{3} \\ n+1 &=& \frac{9b^2+6b+3}{3} \\ n+1 &=& 3b^2+2b+1 \\ n+1 &=& b^2 + b^2 + b^2 +2b+1 \\ n+1 &=& b^2 + b^2 + (b+1)^2\\ \end{array} }\)

 

So n + 1 is the sum of three perfect squares and \(b = \frac{a-1}{3}\).

 

2. We substitute \(a = 3b+2\)

\(\small{ \begin{array}{rcl} n+1 &=& \frac{a^2+2}{3}\qquad \text{substitute }\ a = 3b+2\\ n+1 &=& \frac{(3b+2)^2+2}{3} \\ n+1 &=& \frac{9b^2+12b+4+2}{3} \\ n+1 &=& \frac{9b^2+12b+6}{3} \\ n+1 &=& 3b^2+4b+2 \\ n+1 &=& b^2 + b^2 + b^2 +2b+2b+1+1 \\ n+1 &=& b^2 + b^2+2b+1 + b^2 +2b+1 \\ n+1 &=& b^2 +(b+1)^2+(b+1)^2\\ \end{array} }\)

 

So n + 1 is the sum of three perfect squares and \(b = \frac{a-2}{3}\).

 

Example 1:

\(\small{ \begin{array}{rcl} a &=&7 \\ 3n+1 =a^2&=& 7^2 \qquad \rightarrow \qquad n=\frac{a^2-1}{3}=\frac{49-1}{3} = 16\\\\ n+1 &=& 16+1=17 \\ 17 &=& b^2+b^2+(b+1)^2 \qquad a=3b+1 \qquad \rightarrow b = \frac{a-1}{3} = \frac{7-1}{3} = 2\\ 17 &=& 2^2+2^2+3^2 = 4+4+9\\ \end{array} }\)

 

Example 2:

\(\small{ \begin{array}{rcl} a &=&8 \\ 3n+1 =a^2&=& 8^2 \qquad \rightarrow \qquad n=\frac{a^2-1}{3}=\frac{64-1}{3} = 21\\\\ n+1 &=& 21+1=22 \\ 22 &=& b^2+(b+1)^2+(b+1)^2 \qquad a=3b+2 \qquad \rightarrow b = \frac{a-2}{3} = \frac{8-2}{3} = 2\\ 22 &=& 2^2+3^2+3^2 = 4+9+9\\ \end{array} }\)

 

 

laugh

heureka  Nov 27, 2015
edited by heureka  Nov 27, 2015
edited by heureka  Nov 27, 2015
 #1
avatar+20549 
+35
Best Answer

If 3n + 1 is a perfect square, show that n + 1 is the sum of three perfect squares.

 

3n + 1 is a perfect square:

\(\small{ \begin{array}{rcl} 3n+1 &=& a^2 \\ 3n &=& a^2 - 1 \\ n &=& \frac{a^2-1}{3}\\ \hline n+1 &=& \frac{a^2-1}{3} +1 \\ n+1 &=& \frac{a^2-1+3}{3}\\ n+1 &=& \frac{a^2+2}{3}\\ \end{array} }\)

 

Because \(\frac{a^2+2}{3}\) is a integer then \(a^2+2\) is divisible by 3, then \(a^2\) is not divisible by 3  and also \(a\) is not divisible by 3,

because if 3 is not a prime factor in \(a^2\) a perfect spuare, then 3 is not a prime factor in  \(a\)

 

Two numbers are not divisible by 3. It is  \(3b +1\) and \(3b + 2\)

 

1. We substitute \(a = 3b+1\)

\(\small{ \begin{array}{rcl} n+1 &=& \frac{a^2+2}{3}\qquad \text{substitute }\ a = 3b+1\\ n+1 &=& \frac{(3b+1)^2+2}{3} \\ n+1 &=& \frac{9b^2+6b+1+2}{3} \\ n+1 &=& \frac{9b^2+6b+3}{3} \\ n+1 &=& 3b^2+2b+1 \\ n+1 &=& b^2 + b^2 + b^2 +2b+1 \\ n+1 &=& b^2 + b^2 + (b+1)^2\\ \end{array} }\)

 

So n + 1 is the sum of three perfect squares and \(b = \frac{a-1}{3}\).

 

2. We substitute \(a = 3b+2\)

\(\small{ \begin{array}{rcl} n+1 &=& \frac{a^2+2}{3}\qquad \text{substitute }\ a = 3b+2\\ n+1 &=& \frac{(3b+2)^2+2}{3} \\ n+1 &=& \frac{9b^2+12b+4+2}{3} \\ n+1 &=& \frac{9b^2+12b+6}{3} \\ n+1 &=& 3b^2+4b+2 \\ n+1 &=& b^2 + b^2 + b^2 +2b+2b+1+1 \\ n+1 &=& b^2 + b^2+2b+1 + b^2 +2b+1 \\ n+1 &=& b^2 +(b+1)^2+(b+1)^2\\ \end{array} }\)

 

So n + 1 is the sum of three perfect squares and \(b = \frac{a-2}{3}\).

 

Example 1:

\(\small{ \begin{array}{rcl} a &=&7 \\ 3n+1 =a^2&=& 7^2 \qquad \rightarrow \qquad n=\frac{a^2-1}{3}=\frac{49-1}{3} = 16\\\\ n+1 &=& 16+1=17 \\ 17 &=& b^2+b^2+(b+1)^2 \qquad a=3b+1 \qquad \rightarrow b = \frac{a-1}{3} = \frac{7-1}{3} = 2\\ 17 &=& 2^2+2^2+3^2 = 4+4+9\\ \end{array} }\)

 

Example 2:

\(\small{ \begin{array}{rcl} a &=&8 \\ 3n+1 =a^2&=& 8^2 \qquad \rightarrow \qquad n=\frac{a^2-1}{3}=\frac{64-1}{3} = 21\\\\ n+1 &=& 21+1=22 \\ 22 &=& b^2+(b+1)^2+(b+1)^2 \qquad a=3b+2 \qquad \rightarrow b = \frac{a-2}{3} = \frac{8-2}{3} = 2\\ 22 &=& 2^2+3^2+3^2 = 4+9+9\\ \end{array} }\)

 

 

laugh

heureka  Nov 27, 2015
edited by heureka  Nov 27, 2015
edited by heureka  Nov 27, 2015
 #2
avatar+92429 
+5

Very nice, heureka.......!!!!

 

 

cool cool cool

CPhill  Nov 27, 2015

29 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.